Pengembangan Pusat Misi Pemeliharan Perdamaian Tentara Nasional Indonesia sebagai Center of Peacekeeping training di Asia Tenggara - Pramudya, Dylan (Universitas Perrtahanan Indonesia (UNHAN), 2021)
Post-World War II to 1945, United Nations (UN). Present and become an inter-state organization that then aspires to help maintain world peace. Up to the Department of Peacekeeping Operation (DPKO), the United Nations, Indonesia is a very active country participating in maintaining world peace. The TNI Peacekeeping Mission Center (PMPP TNI) is then a means to carry out planning and preparation of TNI personnel in assignments, training and education related to UN peacekeeping work, both at home and abroad, and how to preparePMPPTNI to be a peacekeeping training center Southeast Asia. Then the purpose of the research is to analyze how the PMPP-TNI readiness and the factors that influence the TNI PMPP to become the main peacekeeping training center in Asia. This research is done by using qualitative method. Primary data were obtained through interviews with 7 informants including academics, practitioners and experts in related fields, while secondary data were obtained from literaturesuch as books, journals, scientific papers and mass media. This study uses the concept of CCP development and the concept of defense diplomacy.The results of this study show that, Indonesia's involvement in Peace Operation is an active role of the State in carrying out Defense Diplomacy. Almost every country that becomes an active contributor to peacekeeping forces has a training center that actively continues to prepare and train the troops to be deployed on the task of peacekeeping operations. With all the advantages possessed through data comparison, the TNI PMPP can be said to be one of the peacekeepingtraining centers in Southeast Asia that has the largest and most comprehensive facilities in line with the UNDPKO standards on the practice area. Facilities contained in the TNI PMPP can not be separated from the vision of the Indonesian government who want to make the PMPP TNI as a World class Peacekeeper center.Keywords: UNDPKO,PMPPTNI, Defense Diplomacy, UN.